OPTIMIZATION OF THE PROCESS FOR OBTAINING L-TYPE ZEOLITES FROM ANGREN KAOLIN RAW MATERIAL - Turabov Bahodir Alikul ugli (Ethiopian International Journal of Multidisciplinary Research, 2026)
The article presents the possibility of obtaining microporous adsorbents using Angren kaolin. Structural changes in kaolin during extraction with an adsorbent were also studied. A scheme for obtaining L-sorbents is presented.